SYNTHESIS KALIUM ALUMUNIUM SULPHATE (ALUM) FROM ALUMUNIUM FOIL WASTE USING KOH AND H2SO4 - Atiqa Rahmawati (Politek ATK Yogyakarta Press, 2023)
The increase in the culinary industry certainly must be balanced with the packaging waste generated. The waste from aluminum foil is one of the wastes produced. Over 8 tons of aluminum foil waste are generated each month in East Java. Waste that has been piled up is only given to third parties. It takes about 400 years for aluminum foil to breakdown and decompose in the soil. Aluminum foil waste can generate environmental pollution. As waste pollution increases, alternatives are needed to convert waste into useful materials. Aluminum foil can be utilized as a raw material for the production of potassium aluminum sulfate due to its high aluminum content. The objective of this study is to utilize aluminum waste into potassium aluminum sulfate. The concentrations of KOH and H2SO4 are the two variables combined. In this study, the yield value, pH analysis, melting point, and Al2O3 content of alum will be determined. The results showed that 2 M KOH and 4.5 M H2SO4 had the highest yield of 88.3580, pH 3,08; melting point 92 °C; and Al2O3 concentration 15,5%. Potassium aluminum sulfate performed physical analysis, including analyses of pH, melting point, and Al2O3 concentration. Alum has a pH of about 3, and its melting point is between 92 and 93 °C, while the Al2O3 content ranges between 9 and 11%. Kalium alumnium sulfate meets the SNI 0032:2011 standards for physical pH and melting point analysis. However, the Al2O3 content does not meet to SNI 0032:2011.